Health providers’ experiences, perceptions and readiness to provide HIV services to men who have sex with men and female sex workers in Uganda – a qualitative study - Matovu, Joseph K. B.; Musinguzi, Geofrey; Kiguli, Juliet; Nuwaha, Fred; Mujisha, Geoffrey; Musinguzi, Joshua; Arinaitwe, Jim; Wanyenze, Rhoda K. (BMC infectious diseases, 2019)
Access to HIV services among men who have sex with men (MSM) and female sex workers (FSWs) remains suboptimal globally. While the reasons for this dismal performance have been documented, limited evidence exists on the experiences, perceptions and readiness of health providers to provide HIV services to MSM and FSWs. Methods: This analysis uses data collected from 48 key informants (health providers in public and private health facilities) as part of a larger study conducted in 12 districts of Uganda between October and December 2013. Data were collected on health providers’ experiences and readiness to provide HIV services to MSM and FSWs and their perceptions on the effect of existing legislation on HIV services provision to MSM and FSWs. Data were captured verbatim, transcribed and analyzed following a thematic framework approach. Results: All health providers reported that they had ever provided HIV services to FSWs and a majority of them were comfortable serving them. However, no health provider had ever served MSM. When asked if they would be willing to serve MSM, nearly three-quarters of the health providers indicated that they would be bound by the call of duty to serve them. However, some health providers reported that they “would feel very uncomfortable” handling MSM because they engage in “a culture imported into our country”. A majority of the health providers felt that they did not have adequate skills to effectively serve MSM and called for specific training to improve their clinical skills. There were mixed reactions as to whether existing criminal laws would affect MSM or FSWs access to HIV services but there was agreement that access to HIV services, under the existing laws, would be more constrained for MSM than FSWs since society “does not blame FSWs [as much as it does] with MSM”.
Keywords: Perceptions; Experiences; Health providers; MSM; FSWs; Uganda